(untitled) (Proceedings of Southern Federal University. Philology, 2016)
Li Feixiang (Southern Federal University, Rostov-on-Don, Russian Federation) The article is devoted to the research of the phenomenon of microblogging, which is an essential part of Chinese culture media. Microblog is considered as an innovative genre of Internet-journalism and as a kind of media text, since in many cases it is also the fact of mass communication and multimedia products, which involves different ways of transmitting information: verbal, visual and audiovisual. Specific examples demonstrate specificity of realization of media categories in the texts of the Chinese microblogging, it is analyzed the characteristics of the combination of diverse components of the text: the actual verbal, visual static and dynamic visual. The classification of the nature of microblogging used in multimedia is given. It is differentiated the following types of microblogging: monocomponent polycoded microblogging, two-component polycoded microblogging with static iconic element, two-component polycoded microblogging with dynamic visual component, multi-component monocoded and polycoded microblogging, including a hyperlink. The role of hyperlinks and the actual verbal component in microblogging is considered. Hyperlink promotes expansion of the boundaries of the text and implies to overcome technical limitations, reduce the amount of information transmitted. Actually verbal text conveys the author’s emotions, but also acts as a metatext in relation to the static or dynamic images. Key words: media, media text, multimedia, microblogging, polycode text, media convergence. DOI: 10.18522/1995-0640-2016-4-170-178